PENGARUH KOMPENSASI FINANSIAL DAN NON FINANSIAL TERHADAP KINERJA KARYAWAN PADA PT. TEGAL JAYA MAKMUR SEJAHTERA - Muhamad Husni Iskandar; Devi Luthfiana Suwarno (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The purpose of this study was to determine the effect of financial compensation and non-financial compensation on the performance of employees of PT. Tegal Jaya Makmur Sejahtera. The method of data collection is done through a questionnaire distributed to employees of PT. Tegal Jaya Makmur Sejahtera. Samples were taken by 75 respondents using random sampling technique. The data obtained were then processed using the SPSS version 24 tool. This analysis included validity tests, reliability tests, normality tests, statistical tests through the F, t test as well as the coefficient of determination (R2) and classical assumption tests. The results of the F test indicate that financial compensation and non-financial compensation simultaneously have a positive effect on employee performance. The t test results show that financial compensation partially has a positive effect on employee performance, while non-financial compensation partially affects employee performance. The R2 test shows the Adjusted R Square of 0.386, which means 38.6% of the factors that affect financial compensation and non-financial compensation, while the remaining 61.4% is influenced by variables outside the research model.